Preimplantation genetic testing for aneuploidy in severe male factor infertility: protocol for a multicenter randomised controlled trial - Li Wang; Li Jin; Yao Lu; Chen Zhang; He-Feng Huang; Yun Sun; Xian-hua Lin; Meng-xi Guo; Dan-dan Wu; Jian-lin Zhang; Cheng-liang Zhou; Chen-ming Xu; et al. (BMJ Open)
Introduction Conventional intracytoplasmic sperm injection (ICSI) is a widely used treatment for couples with severe male infertility. However, there are controversies regarding the selection and the damage to gametes during the ICSI procedure. Although preimplantation genetic testing for aneuploidies (PGT-A) can give genetic information about embryos for transfer and improve fertility rate, and it is widely used in women with recurrent spontaneous abortion or advanced age, PGT-A is not only more expensive but also has unclear effectiveness with respect to the improvement of fertility rate among couples with severe male infertility. High-quality, well-powered randomised clinical trials (RCTs) comparing ICSI+PGT-A and ICSI are lacking.Methods and analysis This is a protocol for a multicenter, open-label RCT in four reproductive medical centers qualified for PGT technique in China. We will study couples with severe male infertility scheduled for their fertility treatment. After the blastocyst culture, eligible participants are randomised to the ICSI+PGT-A group or the conventional ICSI group in a 1:1 ratio. Other assisted reproductive procedures are similar and parallel between the two groups. The primary outcome will be live birth rate and cumulative live-birth rate . Secondary outcomes will be embryo implantation rate, biochemical pregnancy rate, clinical pregnancy rate, spontaneous abortion rate, ongoing pregnancy rate, preterm birth rate, fetal chromosomal abnormality rate, birth defect rate and treatment complications. To demonstrate or refute a difference between the two groups, we plan to include 188 participants in each group; taking consideration of 20% of dropout, the total target sample size is 450.Ethics and dissemination Ethical approval was obtained from International Peace Maternity and Child Health Hospital of Shanghai Jiao Tong University Medical Science Research Ethics Committee (GKLW2016-16). Informed consent will be obtained from each participant. The findings will be disseminated to the public through conference presentations and publication in peer-reviewed scientific journals.Trial registration number ClinicalTrials.gov, NCT02941965.